Study on Effectiveness of Extensive TRUS Guided Prostate Biopsy in Detection of Cancer Prostate - Kiran, P. Usha; Krishna, S. Venkata (New Visions in Medicine and Medical Science Vol. 10, 2024)
Introduction: Prostate cancer has been the most common non-cutaneous malignancy in men and now accounting for one-quarter of all such cancers. Use of Trans Rectal Ultrasonography (TRUS) in men with an abnormal PSA and/or digital rectal examination acting as a guide to direct prostate biopsies will lead to a decrease in the number of early deaths. Materials and Methods: It is a prospective observational study. All the patients attending the Urology clinics or emergency services with LUTS and with a suspicion of Ca prostate on DRE or serum PSA were enrolled in the study. TRUS-guided biopsy was done in all study patients for abnormality on DRE and or an elevated serum PSA level. The statistical analysis was executed by SPSS version 20. Categorical variables were analyzed with "Chi-square test". Results: In the present study, of 95 men, 53 men underwent 10-core biopsy and 42 men underwent 16-core biopsy. Among 95 patients subjected to TRUS guided prostate biopsy, prostatic adenocarcinoma was detected in 31 (32.6%), High-grade PIN in 12 (12.62%), fibroadeno leiomyomatous hyperplasia in 30 (31.57%), fibroadeno leiomyomatous hyperplasia with chronic prostatitis in 5 (5.20%) and chronic prostatitis in 15 (15.78%). Conclusion: The cancer detection rate is high when abnormalities are found in both DRE and PSA compared to elevated PSA alone (70% vs.15%). The detection rate with 16-core TRUS guided biopsy is significantly higher than 10-core biopsy (54.76% vs. 15.09%, P value 0.0037).